Pembinaan Bahasa Indonesia: Bagaimana Strateginya di Era Digital? - Sudaryanto Sudaryanto (Jurnalistrendi : Jurnal Linguistik, Sastra dan Pendidikan, 2019)
The Language and Book Development Agency (formerly the Language Development and Coaching Agency; the popular Language Body) has one vision, which is to increase the involvement of stakeholders in language and literature development. This paper aims to describe strategies for fostering Indonesian language in the digital age, specifically the use of social media and popular culture for the young generation (read: millennial generation) today. The research data collection method is an observation method with reading and note taking techniques. Data is taken from uploads in the form of writings published by the Language Board, the East Nusa Tenggara Language Office (NTT), and the West Nusa Tenggara Language Office (NTB) regularly on social media. The results showed that the Language Body, the NTT Language Office, and the NTB Language Office carried out a strategy of fostering Indonesian language by publishing writings in a number of rubrics, such as "Our Words of the Week", "Today's Terms", "Spelling of Today", "Did you know?", And "Matching Terms". The five rubrics were published through a number of social media that can be accessed by the Indonesian people as Indonesian users.